Ab initio quantum Monte Carlo simulation of the warm dense electron gas - Dornheim,T; Groth,S; Malone,FD; Schoof,T; Sjostrom,T; Foulkes,WMC; Bonitz,M (Physics of Plasmas, 2017)
Warm dense matter is one of the most active frontiers in plasma physics due to its relevance for denseastrophysical objects as well as for novel laboratory experiments in which matter is being strongly compressede.g. by high-power lasers. Its description is theoretically very challenging as it contains correlated quantumelectrons at nite temperature|a system that cannot be accurately modeled by standard analytical or groundstate approaches. Recently several breakthroughs have been achieved in the eld of fermionic quantum MonteCarlo simulations. First, it was shown that exact simulations of a nite model system (30 : : : 100 electrons)is possible that avoid any simplifying approximations such as xed nodes [Schoof et al., Phys. Rev. Lett.115, 130402 (2015)]. Second, a novel way to accurately extrapolate these results to the thermodynamic limitwas reported by Dornheim et al. [Phys. Rev. Lett. 117, 156403 (2016)]. As a result, now thermodynamicresults for the warm dense electron gas are available that have an unprecedented accuracy on the order of0:1%. Here we present an overview on these results and discuss limitations and future directions.